Challenges in the Analysis of Historic Concrete: Understanding the Limitations of Techniques, the Variability of the Material and the Importance of Representative Samples. Issue 1 (2nd January 2022) - Wilkie, Simeon; Dyer, Thomas
ABSTRACT: The number of historically-significant concrete structures which require conservation and repair is ever-increasing. The use of unsuitable proprietary materials has led to poor quality repairs of historically-significant structures in the United Kingdom, some of which have resulted in damage to the historic character of the structure and accelerated deterioration of the substrate. As a result, the approach to the repair of historic concrete structures has shifted from the use of mass-produced proprietary repair materials to purpose-made 'like-for-like' replacements which, theoretically, have similar mechanical and aesthetic properties. In order to create like-for-like repair materials, the original mix proportions and water/cement (w/c) ratio of the substrate have to be established. However, there are concerns regarding the accuracy of existing techniques and standards used for the analyses of hardened concrete. Furthermore, due to a lack of available material, analyses are often carried out on samples that are much smaller than the minimum requirement for a representative sample, or from areas which are not representative. This paper discusses these issues and hopes to provide information to conservators and analysts on the limitations of techniques, the variability of the material and the importance of representative samples.